A focus on paediatric hypertension - Bassareo, Pier Paolo; Mercuro, Giuseppe (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2015)
Hypertension can begin early in childhood, as occasional increases in blood pressure or abnormal blood pressure responses to physical or emotional stress. High blood pressure in juvenile age is defined as a blood pressure repeatedly above the 95th percentile of specific nomograms. Its worldwide prevalence ranges from 1% to about 10%. The purpose of this paper is to perform an overview about characteristics, diagnosis, risk factors, therapy, and prognosis of paediatric hypertension.